2019
DOI: 10.1108/bij-06-2018-0160
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Lean Six Sigma performance measures: a balanced score card approach

Abstract: Purpose The purpose of this paper is to develop the balance score card (BSC) approach based Lean Six Sigma (LSS) performance measurement system and investigate the critical measures currently practiced by Indian manufacturing organizations. Design/methodology/approach This study offers insights of LSS performance measurement from manufacturing industry. Initially, the BSC-based framework is developed to recognize the adoption of LSS performance measures. Then, the framework is applied to nine Indian manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 109 publications
0
28
0
1
Order By: Relevance
“…Zandhessami and Rahgozar (2018) used the DEMATEL approach. Raval et al (2019) suggested the integration of LSS with Balanced-Scorecard for further effectiveness of LSS. Soti et al (2010) suggested the integration of LSS with TRIZ (theory of inventive problem-solving) for improved results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zandhessami and Rahgozar (2018) used the DEMATEL approach. Raval et al (2019) suggested the integration of LSS with Balanced-Scorecard for further effectiveness of LSS. Soti et al (2010) suggested the integration of LSS with TRIZ (theory of inventive problem-solving) for improved results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BSC has four strategic measurement perspectives, namely, financial performance measures, customer performance measures, internal business process performance measures, and learning and growth performance measures (Kaplan and Norton, 2006). Added by (Raval et al, 2019), BSC's approach to financial measures shows the results of actions taken and nonfinancial measures concentrate on internal processes, customer satisfaction, and innovation and improvement. Therefore, the BSC method provides a major advantage for management, which is only measuring factors that are directly related to organizational strategy and not measuring everything (Punniyamoorthy and Murali, 2008).…”
Section: Strategy Selectionmentioning
confidence: 99%
“…Therefore, the BSC method provides a major advantage for management, which is only measuring factors that are directly related to organizational strategy and not measuring everything (Punniyamoorthy and Murali, 2008). For this reason, BSC is more focused on helping management to add value to the company (Raval et al, 2019).…”
Section: Strategy Selectionmentioning
confidence: 99%
“…LSS assessment method for the performance of the organization can be obtained from the feedback and guides from the planning activities. The assessment method permits the manager to regulate the effective practice to use the resources effectively in the organization (Raval et al , 2019). The process of hospital improvement includes the project objective of reducing the waiting of patients and the percentage of scheduled utilization of staff in the process of hospital activities (Bhat et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%